Factors Influencing Depression among Indonesians during the COVID-19 Outbreak - Sarfika, Rika; Malini, Hema; Putri, Dewi Eka; Buanasari, Andi; Abdullah, Khatijah Lim; Freska, Windy (Nurse Media Journal of Nursing, 2021)
Background: The 2019 Coronavirus pneumonia disease (COVID-19) has gained intense attention globally, including in Indonesia. The rapid transmission and clinical effects of the virus can cause depression in Indonesian society. However, information on risk factors for depression during COVID-19 in this country is not known.Â Purpose: This study aimed to determine the level of depression and identify factors influencing depression in Indonesian society during the COVID-19 outbreak.Methods: An online-based cross-sectional study was conducted among Indonesian society aged â‰¥12 years old in April 2020. A total of 1,622 participants from 34 provinces in Indonesia were involved in this study and completed the online questionnaires on demographics, social media exposure, self-rated health, and depression levels with the WHO-Five Well-being Index (WHO-5). Ordinal logistic regression analysis was used to identify the factors associated with depression levels.Results: Of the total sample analyzed, the overall prevalence of depression levels was 28.5% mild depression, 18.4% moderate depression, and 24.8% severe depression. Social media exposure (SME), age, gender, occupation, and self-rated health (SRH) were significantly influencing depression (p<0.05). The factor that most influenced the level of depression was self-rated health (p=0.0001; OR=2.72).Conclusion: This study highlights depression in Indonesian society during the COVID-19 pandemic and provides an understanding of the effects of demographics, social media exposure, and self-rated health. The study suggests the importance of implementing a multi-disciplinary approach (e.g., a collaboration between mental health nursing and community nursing) to deal with depression.